Inclusion and intellectual disability: special and common schools under the point of view of students themselves - Pacheco Moraes Maturana, Ana Paula [UNESP]; Mendes, Eniceia Goncalves (Editora Univ Federal Parana, Centro Politecnico, 2017)
Considering that under the banner of inclusion school transfers between special and common schools have been taking place throughout national territory, it is necessary to investigate how the public students of these schools perceive this process, since the literature warns about the absence of student participation on the decisions about their schooling process. This work aimed to investigate the thoughts of students with intellectual disabilities (ID) on special and regular schools, taking their school transfers as a scenario, be this transfer from the special to the common school or vice versa. It is a descriptive research with multiple case design that involved the study of five cases of ID students who were transferred. The instruments used for data collection were the Drawing-and-Story procedure with the students and complementary interviews with family members. The analysis of the data allowed us to identify that the students assigned to the special school the role of reception and care, and to the common school a place of learning and knowledge, with awareness that these are two distinct forms of schooling, each with its pros and cons. The analysis of the results shows that the study reached its objectives and brought practical, political and scientific implications related to the schooling of the students with ID, especially when giving voice to the target of the school transfer.
Keywords: Special Education; Students; Intellectual disability; Inclusion